Analisis Desain Aplikasi Mobile dalam Membantu Aktivitas Olahraga Berkelompok - Hariz, Muhammad Naufal (Desainpedia: Jurnal Desain Produk dan Desain Komunikasi Visual, 2022)
During the COVID-19 pandemic, it is quite difficult to carry out activities outside the home such as studying, working, worshiping, and even sports are recommended at home so that there are no gathering activities and direct contact with other people, but people are starting to realize the importance of health so that sports trends have formed since the beginning of the pandemic, and continues to this day, such as cycling, futsal, and badminton. Sports venue rental applications can make it easier for people who want to exercise without having to bother coming to the rental place. The user interface is a liaison for interaction between users and the system, therefore an attractive user interface must be communicative and easily understood by users in order to provide a good experience for users. Visual design that is easy to understand is very important in designing the user interface of the application, because users get convenience and comfort when interacting with the application and the design can help to meet user needs